Use of SOPARC to assess physical activity in parks: do race/ethnicity, contextual conditions, and settings of the target area, affect reliability? - Oriol Marquet (BMC Public Health, 2019)
Abstract Background Since its introduction in 2006, SOPARC (Systematic Observation of Play and Recreation in Communities) has become a fundamental tool to quantify park visitor behaviors and characteristics. We tested SOPARC reliability when assessing race/ethnicity, physical activity, contextual conditions at the time of observation, and settings of target areas to understand its utility when trying to account for individual characteristics of users. Methods We used 4725 SOPARC observations completed simultaneously by two independent observers to evaluate intraclass correlation and agreement rate between the two observers when trying to assess sex, age group, race/ethnicity, and level of physical activity of urban park users in different park settings. Observations were in 20 New York City parks during Spring and Summer 2017 within the PARC3 project. Results Observers counted 25,765 park users with high interobserver reliability (ICC = .94; %Agreement.75). Reliability scores were negatively affected by the population being observed, the intensity of physical activity, and the contextual conditions and settings of the target area at the time of observation. Specific challenges emerged when assessing the combination of physical activity and race/ethnicity. Conclusions SOPARC training should aim to improve reliability when assessing concurrent measures such as physical activity, race/ethnicity, age, and sex. Similarly, observing crowded park areas with many active users areas may require more observation practice hours.